2018
DOI: 10.7554/elife.32595
|View full text |Cite
|
Sign up to set email alerts
|

Geometry of antiparallel microtubule bundles regulates relative sliding and stalling by PRC1 and Kif4A

Abstract: Motor and non-motor crosslinking proteins play critical roles in determining the size and stability of microtubule-based architectures. Currently, we have a limited understanding of how geometrical properties of microtubule arrays, in turn, regulate the output of crosslinking proteins. Here we investigate this problem in the context of microtubule sliding by two interacting proteins: the non-motor crosslinker PRC1 and the kinesin Kif4A. The collective activity of PRC1 and Kif4A also results in their accumulati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 71 publications
6
55
0
Order By: Relevance
“…We have previously shown that MAP65 can organize gliding microtubules into active structures that are reminiscent of cellular architectures in dividing cells 13,14 . MAP65, Ase1, and PRC1 have each been shown to be weakly-associating crosslinkers that can drive microtubule bundling in vitro 15–18 .…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that MAP65 can organize gliding microtubules into active structures that are reminiscent of cellular architectures in dividing cells 13,14 . MAP65, Ase1, and PRC1 have each been shown to be weakly-associating crosslinkers that can drive microtubule bundling in vitro 15–18 .…”
Section: Introductionmentioning
confidence: 99%
“…In this last section, we consider the situation where sliding results in overlap shrinkage. Specifically, we aim to understand in vitro experiments that showed overlaps remaining for several minutes [1], [9], [26]. This phenomenon occurs when the turnover of crosslinkers is slower than sliding, such that crosslinkers accumulate in the overlap.…”
Section: Steady Overlapsmentioning
confidence: 99%
“…In HeLa cells, PRC1 is required for the stabilisation of the anaphase midzone [29], and has recently been observed to locate to the bridging fibres connecting sister k-fibres, suggesting that this protein may also have a role during metaphase [15]. In vitro, diffusible crosslinkers can oppose sliding by molecular motors [1], [9], [26]. Being passive in nature, one might have expected the force required to move a head to be proportional to the sliding speed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has examined how antiparallel sliding motors such as kinesin-5 motors, which tend to separate overlapping filaments, and crosslinking proteins from the PRC1/Ase1/MAP65 family, which tend to increase overlap length [16], can balance to give stable overlaps [17][18][19]. Length-regulated overlaps can be created in vitro via crosslinkers and motors that bind to the crosslinkers and exert force on them [20][21][22]. In addition, Bieling and Surrey experimentally demonstrated regulated antiparallel MT overlaps in a system in which little to no sliding occurs [23].…”
mentioning
confidence: 99%